DYNAMICS OF COASTAL DUNES AT CEARÁ STATE, NORTHEASTERN BRAZIL: DIMENSIONS AND MIGRATION RATE - Maia, Luís Parente; Freire, George Satander Sá; de Morais, Jáder Onofre; Rodrigues, Angela Cristina B.; Pessoa, Paulo Roberto; Magalhães, Silvania Helena O. (Arquivos de Ciências do Mar, 2017)
Dimensions and migration rates of mobile dunes, along the Ceará State’s coast, currently composed of sand sheets and barchans, are analysed. The results show that barchans maintain an equilibrium form which can be characterised by values of dimensionless shape parameters H/W and W/L. Dunes are highly mobile, with average migration rates of 17.5 m.yr-1 for barchans and 10 m.yr-1 for sand sheets. The calculated migration rates were found to depend strongly on dune dimensions for both barchans and sand sheets, i.e., the larger the dune is, the lower the migration rate will be. This was associated with the existence of a representative common transport rate along the dune fields which induces a differential geomorphologic response velocity dependent on dune size. Finally, from the observed dune evolution, an aggregatedscale aeolian sediment transport was inferred. This transport rate, in the order of 90-100 m3 /m/yr, is only valid for a time scale from years to decades, which is the one scale used in dune evolution analysis. Finally, some implications of dune migration in the study area are also highlighted.